Influence of the computerized techniques in the methods that are used generally in the teaching of english as a foreign language - Morán Castro, Raúl Ernesto (2006)
Through the years, learning a new language have been something interesting and difficult to accomplish, specially if this language is foreign in Ecuador; for that reason the teaching learning process in a EFL class should be comfortable and dynamic. Besides, there are many factors that participate during the teaching learning process and two common of them are Memory and Emotion , as Krashen (1985) and Stevide (1976) Pedagogic psychologists said: The cognitive side of learning usually gets a great deal of attention, but the affective side of learning is also important . Just in this part, teachers should understand how brains work, with the purpose of creating a new atmosphere in the classroom which could develop the emotional learning of students. Computer software offers an interactive and dynamic way to learn English. It encloses songs, verse, games, dialogs that help students to catch the use of the language in real situations. The best way to teach English is probably a mix of techniques rather than any one technique exclusively. Traditional method is useful to analyze the English grammar structure in a divided way while Interactive methods (songs and verse, games, interactive CDs, among others) are useful to understand the grammar structure in real situation. Besides, interactive methods permit students to practice communication, which, is the principal goal of a language class